Subaxial Lateral Mass Prosthesis for Posterior Reconstruction of Cervical Spine - Jian, Qiang; Liu, Zhenlei; Duan, Wanru; Jian, Fengzeng; Chen, Zan (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2022)
Background Posterior facetectomy or lateral mass resection is often used during cervical dumbbell tumor resection, jeopardizing the stability of cervical spine. The space after resection of one or more lateral masses, if left unfilled might hamper bone fusion and structural support.Purpose There were the aims to obtain the relevant morphometry of the lateral mass of the subaxial cervical spine (C3–C7) and to design a lateral mass prosthesis for the posterior reconstruction of the cervical spine.Methods The computed tomography (CT) scans of healthy volunteers were obtained. RadiAnt DICOM Viewer software (Version 2020.1, Medixant, Poland) was used to measure the parameters of lateral mass, such as height, anteroposterior dimension (APD), mediolateral dimension (MLD), and facet joint angle. According to the parameters, a series of cervical lateral mass prostheses were designed. Cadaver experiment was conducted to demonstrate its feasibility.Results Twenty-three volunteers with an average age of 30.1 ± 7.1 years were enrolled in this study. The height of the lateral mass was 14.1 mm on average. The facet joint angle, APD, and MLD of the lateral mass averaged 40.1 degrees, 11.2 mm, and 12.2 mm, respectively. With these key data, a lateral mass prosthesis consisting of a column and a posterior fixation plate was designed. The column has a 4.0-mm radius, 41-degree surface angle, and adjustable height of 13, 15, or 17 mm. In the cadaver experiment, the column could function as a supporting structure between adjacent facets, and it would not violate the exiting nerve root or the vertebral artery.Conclusion This study provided a detailed morphology of the lateral mass of the subaxial cervical spine. A series of subaxial cervical lateral mass prostheses were designed awaiting further clinical application.
Keywords: cervical vertebral tumor; lateral mass prosthesis; lateral mass morphology; posterior reconstruction; cervical spine